Protected Areas’ Latent Functions and Social Consequences: A Case from Mount Hamiguitan, Philippines - Mendoza, Eva Natividad; Ponce, Roy G.; A. Soria, Sheryl Mae; Amoroso, Victor B. (Forest and Society, 2020)
While protected areas (PAs) are established primarily for biological diversity conservation and provision of ecological services, social dimensions comes into play. This paper extends the discourse on PAs’ impact to local communities by focusing on the latent functions and social consequences utilizing Robert Merton’s Functional Analysis. Based on in-depth interviews among community leaders and elders, and forest custodians around Mount Hamiguitan, a UNESCO World Heritage Site, it is revealed that establishment of PAs entails varied consequences beyond what are being intended and manifested. While communities availed of some latent benefits from the declaration of the PA, they also have responses that limit the success of conservation initiatives. Hence, forest protection is a complex social and political process that demands more integrative response on community’s social, cultural, and political structures and dynamics.